A behavior study of the common tern (Sterna hirundo hirundo L.) - Palmer, Ralph S. (Ralph Simon), 1914-2003. (Boston, Mass., Printed for the Society, 1941)
"Literature cited": p. 111-119. Mode of access: Internet.